Deterinação da biomassa e altura de amostragem para a quantificação de nutrientes em Acacia mearnsii De Wild - Saidelles, Fabio Luiz Fleig (2005)
The objective of this study was to quantify the biomass and to determine the optimal sampling point for nutrients quantification in four year old Acacia mearnsii trees. It was conducted in black wattle stand, located in Arroio dos Ratos city in a farm belonging to SETA S/A, having as coordinates 30° 07 12 of south latitude and 51° 57 45 of longitude, with 90 m of average altitude. The first step was the forest inventory, where 30 trees were felled, distributed in 7 diametric classes, to cover the stand heterogeneity, then the biomass and the nutrients amount in the leaves, live branches, dead branches, roots, wood and bark were determined. Samples of wood and bark were taken along the stem in the posítions of: 1, 3, 10, 20, 30, 40, 50, 60, 70, 80 and 90% of the total height. The total biomass from Acacia mearnsii trees was of 72, 91 Mg ha-1 and was divided in: 64% in the wood, 11% in the roots, 10% in the bark, 7% in the live branches, 5% in the dead branches and 3% in the leaves. The total amount of macronutrients (kg ha-1) were: 384,94 of N, 15,69 of P, 200,06 of K, 267,74 of Ca, 58,54 of Mg and 18,57 of S, and the micronutrients (g ha-1) were: 1.249,01 of B, 195,33 of Cu, 6.485,64 of Fe, 1.073,52 of Mn and 809,33 of Zn. From this total, the leaf component accumulated 20% of the N, 18% of P and Cu, 12% of the K, 5% of Ca and Fe, 10% of Mg and S, 17% of B, 19% of Mn and 6% of Zn; the roots accumulated 14% of N, Cu , Mn and Zn, 11% of P and K, 8% of Ca, 7% of Mg, 15% of S, 17% of B and 66% of Fe; the wood accumulated 21% of N, 27% of P, 30% of K, 50% of Ca, 36% of Mg, 45% of S, 26% of B and Mn, 37% of Cu, 9% of Fe and 41% of Zn; the bark accumulated 22% of N and Mg, 17% of P, 21% of P and Ca, 22% of Mg, 10% of S, Fe and Cu, 20% of B and Mn and 12% do Zn; the dead branches accumulated 8% of N, S and B, 6% of P, 4% of K, 7% of Ca, 11% of Mg, Cu and Zn, 5% of Fe and 9% of Mn; the live branches accumulated15% of N, 21% of P, 22% of K, 9% of Ca, 13% of Mg and B, 12% of S and Mn, 10% of Cu, 5% of Fe and 16% of Zn. The total amount of carbon stored in the biomass was 29,79 Mg ha-1, allocated 64% in the wood, 11% in the roots, 9% in the bark, 7% in the live branches and 4% in the dead branches and leaves. The nutrients Ca, Mg, S, B, Cu, Fe, Mn and Zn didn t show significant difference along the stem to wood and bark, indicating that there isn t an exact point for sampling along the stem to nutrients quantification. The optimal sampling point to nutrients (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn) quantification along the stem should be 50% from the total height in Acacia mearnsii trees